The Effect of Sonication Parameters on the Thickness of the Produced MoS2 Nano-Flakes - Najme Sadat TAGHAVI; Reza AFZALZADEH (Archives of Acoustics, 2021)
Liquid Phase Exfoliation (LPE) is a common route to produce two-dimensional MoS2 nanosheets. In this research, MoS2 powder is exfoliated by an ultrasonic probe (sonicator) in a water-ethanol solution. It is reported that MoS2 as a prototype 2D Transition Metal Dichalcogenide, has a band gap that increases with a decreasing number of layers. There are some factors that affect the average band gap energy value and the thickness of the exfoliated flakes. We varied different parameters of the ultrasonic probe like power, pulse percentage and time duration of sonication to investigate the effects on the number of MoS2 layers. Our findings from the UV-Visible spectra, SEM, FESEM and TEM images indicate that the minimum thickness for these samples was acquired at 50% of the input power of the sonicator we used (65 W) and the optimum pulse percentage is 50%. The current study also found that the average amount of band gap increased with an increase in sonication time, and then remained unchanged after 60 minutes.